Wild card [videorecording (DVD)] - Goldman, William, 1931-2018; Statham, Jason, 1967-; Angarano, Michael; Ventimiglia, Milo, 1977-; Heche, Anne; Vergara, Sofía, 1972-; Alexander, Jason, 1959-; Davis, Hope, 1967-; Tucci, Stanley; Goldman, William, 1931-2018 (Lionsgate, 2015)
A bodyguard goes after the sadistic thug who beat his friend, only to find that the object of his wrath is the son of a powerful mob boss.